Five Steps for Process Development under the Energy Sustainability Criteria (2018)
Considering that sustainability criteria play a fundamental role in the control and efficient operation of production processes, this article presents five fundamental steps based on the benefits of an Integrated Energy Management System. The five steps formulated for the development of processes under a sustainable development approach are based on measures for the rational use of energy that seek both environmental and economic benefits, if these savings measures are applied in the respective production process. The results obtained from the application of the five steps to a company of the product sector in Colombia, resulted in an additional benefit such as increased energy control of the production process. The article shows in detail how to establish the Baseline, evaluate the consumption trend, quantify emission reductions, economically quantify savings, and evaluate the energy control of the production process with a view to the sustainable operation of industrial processes. The main contribution of this article is the development of a systematic tool based on performance indicators and historical operational information of the process to achieve a sustainable and environmentally friendly operation of any company that implements it.